2020
DOI: 10.1186/s12879-020-05352-5
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of cutaneous abscesses caused by Panton-Valentine leukocidin-producing methicillin-susceptible Staphylococcus aureus among gold mine workers, South Africa, November 2017 to March 2018

Abstract: Background We aimed to describe an outbreak of cutaneous abscesses caused by Panton-Valentine leukocidin (PVL)-producing methicillin-susceptible Staphylococcus aureus (MSSA) among gold mine workers. Methods In February 2018, we retrospectively reviewed a random sample of 50 medical records from 243 cases and conducted face-to-face interviews using a structured questionnaire. Pus aspirates were sent to the National Institute for Communicable Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…adult and paediatric wards) were selected for PFGE. PFGE was done as previously described [27,28]. Cluster analysis was done in BioNumerics (GelCompar II Gel Electrophoresis Software, Version 7.6, Applied Math, UK).…”
Section: Pulsed-field Gel Electrophoresismentioning
confidence: 99%
“…adult and paediatric wards) were selected for PFGE. PFGE was done as previously described [27,28]. Cluster analysis was done in BioNumerics (GelCompar II Gel Electrophoresis Software, Version 7.6, Applied Math, UK).…”
Section: Pulsed-field Gel Electrophoresismentioning
confidence: 99%
“…In a recent retrospective study, Rochet et al (2020) have shown that the rate of patients visits for skin abscesses in the emergency department has increased significantly and that S. aureus was the pathogen involved in 73% of these infections (Rochet et al, 2020). Moreover, Ismail et al (2020) have described a large epidemic of skin abscesses among gold mine employers in South Africa. S. aureus PVL was responsible for this epidemic, due to cross-contamination resulting from poor hygiene practices.…”
Section: Skin Infections Skin Infections Skin Infections Skin Infectionsmentioning
confidence: 99%
“…International travel is another risk factor. This has been described, for example, in travelers returning from Africa [ 6 ] or the Americas [ 7 ].…”
Section: Introductionmentioning
confidence: 99%